Breathable & interlock-able roof tile: natural ventilation in tropical humid architecture / Rostam Yaman … [et al.] - Yaman, Rostam; Alias, Zarina; Ahmad, Noraini; Roslan, Rafiudin; Mohd Yusoff, Farran Norizzah (Research Innovation Business Unit, 2014)
Comprehension of microclimate and data analysis is crucial in developing passive architectural solution in tropical region. This project deals with ambient architecture in humid tropical region, the exercise and investigation of natural ventilation efficiency using stack ventilation and buoyancy effect. It also addresses the sustainability and security consideration in term of based material usage and method of installation. The overall idea of the project is to solve four issues. Namely, air movement in the building plays an important role in keeping the building temperature to comfort level in humid tropical region, importance of roof in discharging the hot air out (Based on buoyancy theory) and top plane of an architecture (roof which made from roof tile conventionally) and installation of roof tiles. Thus, this project aims to design a breathable roof plane i.e roof tile so that it will ventilate naturally and at the same time to prevent rain water penetration to the building and develop an interlock-able roof tiles for ease of installation and safe from intrusion by burglar or lifted by natural forces. It also hopes to consider most sustainable and natural material as the based material for the tiles the project novelty to invent a natural air movement and hot air discharge off the building using the existing building envelope (the roof) component. Stack ventilation concept and air buoyancy theory is applied in the project as it will work on the most natural manner and without any artificial mechanical assistance. Each one of the tile pieces is ventilated (air penetrable) but at the same time prevent rain water penetration (profile vent hole) This project is also unique as the interlock-able fixing method eases the installation and at the time will prevent intrusion from burglar or force lifted during any natural disaster. The raw material of the tiles is unglazed natural clay hence it has the property to prevent heat gain thus making the building more sustainable and conserves energy. The installation method is relatively simple and easy as the tile is interlock-able and firmly fixed on roof structure. The mechanics of the air vent and interlock-able profile are capable of being commercialised in humid tropical and sub-tropic regions building industry as a Lock Roof.